Chronic insomnia: clinical and research challenges--an agenda. - Riemann, D; Spiegelhalder, K; Espie, C; Pollmächer, T; Léger, D; Bassetti, C; van Someren, E (2011)
Chronic insomnia afflicts up to 10% of the population in Western industrialized countries. It is characterized by delayed sleep onset, problems in maintaining sleep, early morning awakening or the feeling of non-restorative sleep coupled with significant daytime impairments on an emotional, social or professional level. It can occur as a co-morbid condition in any other medical or mental disorder, but also as a primary condition. Within the last decade new diagnostic and differential diagnostic approaches have been suggested that enhance diagnostic precision. Epidemiological data and data relating to the health care and cost situation of chronic insomnia suggest a huge burden for society. Chronic insomnia leads to a clear-cut increased risk for psychopathology (i. e., affective disorders) and probably also for cardiovascular and metabolic dysfunction. The pathophysiology of the condition is still poorly understood and will profit from integrating modern neuroscientific approaches (animal studies, molecular biology, neuroimaging, neurophysiology, etc.). Current treatment strategies are mainly based on cognitive behavioural interventions (CBT-I) and hypnotic treatment with benzodiazepine receptor agonists and sedating antidepressants. Although the effectiveness of these treatments has been clearly demonstrated, a substantial proportion of patients proves to be treatment-resistant or profits only poorly. The question of long-term pharmaceutical treatment of chronic insomnia, at least in Europe, is unresolved and urgently needs answers. Novel rational treatment avenues require clues on causes and mechanisms from integrated neuroscientific approaches. The important issues concerning insomnia treatment in the future especially in Europe will be reviewed and discussed critically.